Operational electrochemical stability of thiophene-thiazole copolymers probed by resonant Raman spectroscopy. - Wade,J; Wood,S; Beatrup,D; Hurhangee,M; Bronstein,H; McCulloch,I; Durrant,JR; Kim,JS (Journal of Chemical Physics, 2015)
We report on the electrochemical stability of hole polarons in three conjugated polymers probed by resonant Raman spectroscopy. The materials considered are all isostructural to poly(3-hexyl)thiophene, where thiazole units have been included to systematically deepen the energy level of the highest occupied molecular orbital (HOMO). We demonstrate that increasing the thiazole content planarizes the main conjugated backbone of the polymer and improves the electrochemical stability in the ground state. However, these more planar thiazole containing polymers are increasingly susceptible to electrochemical degradation in the polaronic excited state. We identify the degradation mechanism, which targets the C=N bond in the thiazole units and results in disruption of the main polymer backbone conjugation. The introduction of thiazole units to deepen the HOMO energy level and increase the conjugated backbone planarity can be beneficial for the performance of certain optoelectronic devices, but the reduced electrochemical stability of the hole polaron may compromise their operational stability.